Chylopericardium in a child with IgA nephropathy: a case report - Kang, Yu-lin (BMC Pediatr, 2018)
BACKGROUND: Chylopericardium effusion is characterized by the accumulation of milky effusion in the pericardium. It is often idiopathic but it can be secondary to trauma, chest radiation, tuberculosis and malignancy. If cardiac tamponade ensues, it becomes life-threatening. Herein we describe chylopericardium tamponade in a child with IgA nephropathy. To the best of our knowledge, this is the first reported case of chylopericardium tamponade in IgA nephropathy. CASE PRESENTATION: A 6 years old boy with IgA nephropathy presented with dyspnea, orthopnea, pretibial pitting edema, ascites and fever. Muffled heart sounds and hepatomegaly were also noted. Echocardiography and thoracic CT revealed that there was a large volume of hydropericardium. Moreover, the pericardial milky fluid by pericardiocentesis was analyzed and chylopericardium effusion was eventually confirmed. Pericardial drainage was continued and his diet was modified to low fat, rich MCT and high protein. Complete remission was achieved after 3 weeks of this combined treatment. CONCLUSION: Chylopericardial tamponade could be a rare and life-threatening complication of IgA nephropathy. Etiological analysis is critical for determining the therapeutic approach in patients with pericardial effusion.